The Impact of Dietary Analyzed Calcium to Phosphorus Ratios and Standardized Total Tract Digestible Phosphorus to Net Energy Ratios on Growth Performance, Bone, and Carcass Characteristics of Pigs - Hadley R. Williams; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Carine M. Vier; Ning Lu; Ron Navales; Matthew Spindler; Uislei Orlando; Luis Zaragoza; et al. (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 2,184 pigs (PIC 337 × 1050; initially 27.3 lb) were used to evaluate the effects of feeding varying analyzed calcium to phosphorus (Ca:P) ratios at two levels of standardized total tract digestible (STTD) P:NE. Pens of pigs (26 pigs per pen) were assigned to 6 dietary treatments in a randomized complete block design with 14 pens per treatment. Diets consisted of two levels of STTD P:NE, including the PIC recommendation (1.8, 1.62, 1.43, 1.25, 1.10, and 0.99 g STTD P/Mcal NE from 25 to 50, 50 to 90, 90 to 130, 130 to 180, 180 to 230, and 230 to 280 lb, respectively); or 75% of the PIC recommendation, and 3 analyzed Ca:P ratios: 0.90:1, 1.30:1, and 1.75:1. Diets were corn-soybean meal-based and contained phytase (Quantum Blue G, AB Vista, Marlborough, Wiltshire, UK); 500 to 210 FTU/kg with release values from 0.13 to 0.07% STTD P. There was a Ca:P × STTD P:NE interaction (P<0.05) observed for average daily gain (ADG), feed efficiency (F/G), and final body weight (BW). For ADG and final BW, when feeding 75% of PIC STTD P recommendation, increasing the analyzed Ca:P ratio decreased ADG and final BW (linear,P<0.001). However, when feeding the PIC STTD P recommendation, increasing the analyzed Ca:P ratio tended to improve ADG and final BW (linear,P<0.10). For F/G, when feeding 75% of the PIC STTD P recommendation, increasing the analyzed Ca:P ratio tended to worsen F/G (linear,P<0.10), whereas in pigs fed diets that met PIC STTD P recommendations, increasing the analyzed Ca:P ratio tended to improve F/G in a quadratic (P<0.10) manner. Despite the interactions, pigs fed the PIC STTD P recommendations had increased ADG, final BW, and improved F/G compared to pigs fed 75% of PIC STTD P recommendations (P<0.001). In summary, pigs fed at PIC STTD P recommendations had improved overall ADG and F/G compared to pigs fed diets at 75% of PIC STTD P recommendations. Additionally, increasing the analyzed Ca:P ratio worsened ADG and F/G when STTD P was below PIC recommendations but had marginal impacts when adequate STTD P was fed.
Keywords: calcium; growth performance; phosphorus; pigs